Atractylodes lancea (Thunb.) DC. [Asteraceae] rhizome-derived exosome-like nanoparticles suppress lipopolysaccharide-induced inflammation in murine microglial cells - Kawada, Kei; Ishida, Tomoaki; Morisawa, Shumpei; Jobu, Kohei; Higashi, Youichirou; Aizawa, Fuka; Yagi, Kenta; Izawa-Ishizawa, Yuki; Niimura, Takahiro; Abe, Shinji; Goda, Mitsuhiro; Miyamura, Mitsuhiko; et al. (Frontiers in Pharmacology, 2024)
Background: Exosome-like nanoparticles (ELNs) mediate interspecies intercellular communications and modulate gene expression.Hypothesis/Purpose: In this study, we isolated and purified ELNs from the dried rhizome of Atractylodes lancea (Thunb.) DC. [Asteraceae] (ALR-ELNs), a traditional natural medicine, and investigated their potential as neuroinflammatory therapeutic agents.Methods: ALR-ELN samples were isolated and purified using differential centrifugation, and their physical features and microRNA contents were analyzed through transmission electron microscopy and RNA sequencing, respectively. BV-2 microglial murine cells and primary mouse microglial cells were cultured in vitro, and their ability to uptake ALR-ELNs was explored using fluorescence microscopy. The capacity of ALR-ELNs to modulate the anti-inflammatory responses of these cells to lipopolysaccharide (LPS) exposure was assessed through mRNA and protein expression analyses.Results: Overall, BV-2 cells were found to internalize ALR-ELNs, which comprised three microRNAs (ath-miR166f, ath-miR162a-5p, and ath-miR162b-5p) that could have anti-inflammatory activity. Pretreatment of BV-2 cells with ALR-ELN prevented the pro-inflammatory effects of LPS stimulation by significantly reducing the levels of nitric oxide, interleukin-1β, interleukin-6, and tumor necrosis factor-α. Notably, the mRNA levels of Il1b, Il6, iNos, ccl2, and cxcl10 in BV-2 cells, which increased upon LPS exposure, were significantly reduced following ALR-ELN treatment.Moreover, the mRNA levels of heme oxygenase 1, Irf7, ccl12, and Irg1 also increased significantly following ALR-ELN treatment. In addition, pretreatment of primary mouse microglial cells with ALR-ELN prevented the pro-inflammatory effects of LPS stimulation by significantly reducing the levels of nitric oxide.Our findings indicate that ALR-ELNs exhibit anti-inflammatory effects on murine microglial cells. Further validation may prove ALR-ELNs as a promising neuroinflammatory therapeutic agent.